2012
DOI: 10.5897/jidi11.049
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A H1NI (Pandemic 2009): How prepared are healthcare providers in Calabar, Nigeria?

Abstract: , an outbreak of influenza was reported in Mexico and California and within months, it spread to all continents of the world. An influenza pandemic has always posed a threat to global public health. The objective of this study was to assess the knowledge, attitude, reported practice and preparedness of health care providers in Calabar, Nigeria, regarding the H1N1 pandemic. This was a prospective study. A semi-structured questionnaire was administered on health care providers in Calabar, Nigeria. One hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…Our study demonstrated that 61% of the nurses were willing to provide nursing care for a patient in the ICU during the COVID-19 pandemic. These results are higher than in previous studies ( Wong et al, 2010 , Etokidem et al, 2012 , Damery et al, 2009 , Irvin et al, 2008 ) where willingness to care during a pandemic ranged from 23% ( Wong et al, 2010 ) to 50% ( Irvin et al, 2008 ). Conversely, a study ( Ma et al, 2011 ) conducted in an ICU in China reported a high (82.3%) willingness to care during the H1N1 influenza pandemic.…”
Section: Discussioncontrasting
confidence: 77%
“…Our study demonstrated that 61% of the nurses were willing to provide nursing care for a patient in the ICU during the COVID-19 pandemic. These results are higher than in previous studies ( Wong et al, 2010 , Etokidem et al, 2012 , Damery et al, 2009 , Irvin et al, 2008 ) where willingness to care during a pandemic ranged from 23% ( Wong et al, 2010 ) to 50% ( Irvin et al, 2008 ). Conversely, a study ( Ma et al, 2011 ) conducted in an ICU in China reported a high (82.3%) willingness to care during the H1N1 influenza pandemic.…”
Section: Discussioncontrasting
confidence: 77%
“…For instance, during the H1N1 influenza pandemic in China, more than 82% of the HCWs expressed willingness to care for H1N1 patients [28]. The rate was 82% in Australia [29] and 85% in Japan [30], though it was comparatively low in some countries like Hong Kong (23%) [31] and Nigeria (34%) [32] during the same pandemic. Studies conducted in the context of a previous avian influenza (H5N1) pandemic reported that the rate of the willingness of the HCWs to continue work in hospitals was 84% in the USA [33], 90% in Japan [34] and 57% in Taiwan [18].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, around 21% of HCWs of selected hospitals of Southwest Ethiopia were unwilling to work [ 11 ]. In other past studies of HCWs’ willingness to work in a pandemic, like the H1N1 influenza pandemic, up to 20% showed hesitation to work in China [ 12 ], while in other countries like Nigeria and Hong Kong, the percentages were at 66 and 77 respectively [ 13 , 14 ]. According to the study by Tahir et al, HCWs experience a high level of stress, depression, and anxiety during these periods of physical and mental overload during the pandemic which have long-term psychological impacts on their work and personal lives [ 15 ].…”
Section: Introductionmentioning
confidence: 99%